Prenatal hyperhomocysteinemia induces oxidative stress and accelerates 'aging' of mammalian neuromuscular synapses. Issue 75 (June 2019) - Khuzakhmetova, Venera; Yakovleva, Olga; Dmitrieva, Svetlana; Khaertdinov, Nail; Ziyatdinova, Guzel; Giniatullin, Rashid; Yakovlev, Aleksey; Bukharaeva, Ellya; Sitdikova, Guzel
Highlights: High intensity of quantal release was shown in synapses of neonatal rats with prenatal hHCY. Prenatal hHCY induces synchronization of quantal release in synapses of newborn rats. Synapses of neonates with hHCY are susceptible to inhibitory effects of hydrogen peroxide. Prenatal hHCY is resulted in the appearance of adult-like synapses in newborn rats. Prenatal hHCY induces malfunctioning of the antioxidant defense in rat diaphragm muscle. Abstract: Enhanced levels of homocysteine during pregnancy induce oxidative stress and contribute to many age-related diseases. In this study, we analyzed age-dependent synaptic modifications in developing neuromuscular synapses of rats with prenatal hyperhomocysteinemia (hHCY). One of the main findings indicate that the intensity and the timing of transmitter release in synapses of neonatal (P6 and P10) hHCY rats acquired features of matured synaptic transmission of adult rats. The amplitude and frequency of miniature end-plate currents (MEPCs) and evoked transmitter release were higher in neonatal hHCY animals compared to the control group. Analysis of the kinetics of neurotransmitter release demonstrated more synchronized release in neonatal rats with hHCY. At the same time lower release probability was observed in adults with hHCY. Spontaneous transmitter release in neonates with hHCY was inhibited by hydrogen peroxide (H2 O2 ) whereas in controls this oxidant was effective only in adult animals indicating a higher susceptibility of motor nerve terminals to oxidative stress. The morphology and the intensity of endocytosis of synaptic vesicles in motor nerve endings was assessed using the fluorescence dye FM 1-43. Adult-like synapses were found in neonates with hHCY which were characterized by a larger area of presynaptic terminals compared to controls. No difference in the intensity of FM 1-43 fluorescence was observed between two groups of animals. Prenatal hHCY resulted in reduced muscle strength assessed by the Paw Grip Endurance test. Using biochemical assays we found an increased level of H2 O2 and lipid peroxidation products in the diaphragm muscles of hHCY rats. This was associated with a lowered activity of superoxide dismutase and glutathione peroxidase. Our data indicate that prenatal hHCY induces oxidative stress and apparent faster functional and morphological "maturation" of motor synapses. Our results uncover synaptic mechanisms of disrupted muscle function observed in hHCY conditions which may contribute to the pathogenesis of motor neuronal diseases associated with enhanced level of homocysteine.